ANTIDIABETIC ACTIVITY OF KARCHURE CHOORANAM ON ALLOXAN INDUCED DIABETIC RATS - K. NANDHAGOPAL; M.KANNIYAKUMARI; J. ANBU; V.VELPANDIAN (International Journal of Pharma and Bio Sciences, 2013)
Phoenix dactylifera linn (Arecaceae) commonly known as Date palm has been widely used in Siddha system of medicine for diabetes. The powder form of dried dates (Karchure chooranam) showed a significant inhibitory effect was screened at 500mg/kg, for the in vivo anti-diabetic activity on alloxan induced diabetic rats. Glibenclamide (10mg/kg) used as reference standard. Single dose (500 mg/kg) treatment with the siddha drug Karchure chooranam produced 69.34% anti-hyperglycaemic effect (antidiabetic effect). The trial drug showed a significant anti-diabetic activity (P<0.01) and were comparable with that of standard thus validating the traditional claim of the plant.